What happens to people's lungs when they get coronavirus disease 2019? - Frizzelli, Annalisa; Tuttolomondo, Domenico; Aiello, Marina; Majori, Maria; Bertorelli, Giuseppina; Chetta, Alfredo (Acta Biomedica Atenei Parmensis, 2020)
The novel coronavirus SARS-CoV-2 was first identified in Wuhan in December 2019 as cause of the consequent novel coronavirus disease 2019 (COVID-19). The virus has since spread worldwide. The clinical presentation following human infection ranges from a mild upper respiratory tract infection to severe acute respiratory distress syndrome and sepsis. We reviewed literature using Pubmed to identify relevant English-language articles published until April 15, 2020. Search terms include novel coronavirus pneumonia, severe acute respiratory syndrome coronavirus 2, coronavirus and ventilation. We summarized what SARS-CoV-2 infection means for the lungs.